The Emerging Science of Multisystemic Resilience: Trade-offs and Transformations in Contexts of Adversity - Michael Ungar; Alice Koubová (Filozofia)
This paper explores the concept of resilience as much more than a personal capacity to overcome adversity. Using reflections from ontology, ethics and epistemology, this paper offers philosophical contextualisation of resilience thinking and the corresponding paradigm shift. It shows that individual resilience depends on a person’s ability to navigate their way to the resources they need for well-being while making multisystemic resources available in ways that are meaningful. Paradoxically, resilience is a consequence of how these multiple systems interact to support positive development and the feedback loops and trade-offs necessary to ensure that a single system’s success does not compromise the resilience of other systems. Five patterns of resilience are discussed, each a viable solution to coping with stress.